MARKET TYPOLOGY, CONCENTRATION, AND COMPETITION OF NATIONAL MEDIA CONGLOMERATE IN INDONESIA - Bestian Nainggolan (Ikatan Sarjana Komunikasi Indonesia, 2017)
The economic practices of media industry in Indonesia are inseparable from the pattern of oligopolistic market competition and control. This trend is seen from further centralized market control of media, particularly advertising media in a number of media corporate groups. Media corporate groups apply practices of conglomeration in market control with horizontal, vertical, or diagonal integrated strategy. Criticism on these practices is often expressed, but there is no assessment based on the empirical evidence on the business behavior of media conglomeration. This paper explores the characteristics of media conglomerate by reconstructing the typology of media conglomeration introduced by Richard Bounce: Concentric Conglomerates and Diversified Conglomerates, and three models by Graham Murdock: Industrial Conglomerates, Services Conglomerates and Communications Conglomerates. Six typology models of conglomerate are formed, namely (1) Industrial-Concentric; (2) Industrial-Diversified; (3) Services-Concentric; (4) Services-Diversified; (5) Communications-Concentric; (6) Communications-Diversified. The economic performance of each conglomerate group regarding market concentration and market competition in constructing the market structure of media industry is studied based on the typologies. The study finds a new typology model of media conglomerate and manages to prove that national media conglomerate still dominates the media market in Indonesia.Â